Disownership of body parts as revealed by a visual scale evaluation. An observational study. (17th February 2020) - Ronchi, Roberta; Bassolino, Michela; Viceic, Dragana; Bellmann, Anne; Vuadens, Philippe; Blanke, Olaf; Vallar, Giuseppe
Abstract: The disownership of body parts, that most frequently occurs on the left side of the body, contralateral to right-hemispheric lesions, is an infrequent disorder, as usually assessed by interviews asking for dichotomic "yes/no" responses. This observational study in right-brain-damaged stroke patients investigated the efficacy of a continuous Visual Analog Scale (VAS) to detect body disownership after right brain damage, compared to dichotomic questions. Thirty-two right-handed right-brain-damaged stroke patients were given a Standardized Interview (SI), asking " Whose hand/arm/leg is this? ", followed by a VAS (asking patients to mark on a vertical line their agreement with the statement that a body part belonged to them). The neural correlates of this disorder and measures of extra-personal and personal spatial neglect were also assessed. Control data were recorded from 18 neurologically unimpaired right-handed participants. During the interview, no patient showed disownership of body parts. Conversely, on the VAS eight out of 32 (25%) patients' scores, but none of the controls' scores, indicated a judgement of disownership for left body parts, with a left-right difference larger than that of control participants. VAS-detected disownership was not systematically associated with extra-personal and personal unilateral spatial neglect. Lesion sites associated with disownership of left body parts included the caudate nucleus and the anterior part of the internal capsule. To conclude, the VAS task, compared to the interview, is a novel tool to detect disownership of left body parts in right brain-damaged patients. A revised classification of body-ownership disorders is proposed. The present variant, assessed and detected by the VAS task, is termed Covert disownership and distinguished from the Overt disownership assessed by a SI. Highlights: Patients with right-brain-lesion can show « hidden » forms of body disownership. Visual analogue scale is a novel tool to detect body disownership. A new form of body disownership is proposed, termed Covert disownership .